TASHFIYAH, TARBIYAH, DAN TAZKIYATUN NAFS SEBAGAI KONSEP PENDIDIKAN RABBANY (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2019)
Having achieved a series of world prestige, humans are faced with many new problems that are intensely serious. Instead of become settled, the success of reaching the peak of materialistic progress turns out furthering people away from sincerity. In this case, we cannot deny that the western hegemony has had a large role in undermining our eastern values. As the basis of values evolution, education is one of questionable entities related to the merits of a situation or a state. Ironically, the cases emerged these days show that our education is not satisfactory. Therefore, it is time for us to refer to God’s guidance, to return to the concept of rabbani education and to be contended to re-educate the people. It is, of course, for the birth of independent and universal human being, not partial.